2023
DOI: 10.3390/ijms24043914
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of N-Methyl-D-Aspartate (NMDA) Receptors in the Cardiovascular System: Physiological Implications, Pathological Consequences, and Therapeutic Perspectives

Abstract: N-methyl-D-aspartate receptors (NMDARs) are ligand-gated ion channels that are activated by the neurotransmitter glutamate, mediate the slow component of excitatory neurotransmission in the central nervous system (CNS), and induce long-term changes in synaptic plasticity. NMDARs are non-selective cation channels that allow the influx of extracellular Na+ and Ca2+ and control cellular activity via both membrane depolarization and an increase in intracellular Ca2+ concentration. The distribution, structure, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 158 publications
(314 reference statements)
0
5
0
Order By: Relevance
“…NMDAR is extensively distributed in cardiac tissue and plays a crucial role in regulating a range of physiological and pathological mechanisms, including cardioprotection, preconditioning, postconditioning, arrhythmias, hypertrophy, and apoptosis. [18][19][20] Myocardial ischemia is characterized by a deficiency in oxygen and glucose, which hinders the production of ATP and promotes anaerobic glycolysis. Consequently, this metabolic shift leads to acidosis and the accumulation of lactate.…”
Section: Role Of Nmdar In Myocardial Irimentioning
confidence: 99%
See 3 more Smart Citations
“…NMDAR is extensively distributed in cardiac tissue and plays a crucial role in regulating a range of physiological and pathological mechanisms, including cardioprotection, preconditioning, postconditioning, arrhythmias, hypertrophy, and apoptosis. [18][19][20] Myocardial ischemia is characterized by a deficiency in oxygen and glucose, which hinders the production of ATP and promotes anaerobic glycolysis. Consequently, this metabolic shift leads to acidosis and the accumulation of lactate.…”
Section: Role Of Nmdar In Myocardial Irimentioning
confidence: 99%
“…In renal IRI, the expression of NMDAR isoforms and subunits varies in different renal regions and cell types resulting in different sensitivities and severities of renal IRI, and blockade of NMDAR can attenuate renal IRI and protect renal function and structure. [ 17 ] Especially in the cardiovascular system, studies have shown that NMDAR is detected and expressed throughout the cardiovascular system in both the physical and pulmonary circulation, such as the conduction system, cardiomyocytes, pachyderm fibers, sinus node, etc, [ 18 ] and plays different roles.…”
Section: Structure and Distribution Of Nmdarmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional mechanism that enriches the versatility of intracellular Ca 2+ signalling is represented by the spatial location of the Ca 2+ sources, which can be physically coupled to different Ca 2+ -dependent decoders ( Berridge et al, 2003 ; Bagur and Hajnoczky, 2017 ; Ong et al, 2019 ; Barak and Parekh, 2020 ). Environmental cues generate a complex choreography of intracellular Ca 2+ signals ( Berridge et al, 2003 ; Clapham, 2007 ), whose spatio-temporal malleability enables one single ion messenger to control as many different functions as fertilization ( Moccia et al, 2006 ), cell cycle ( Lim et al, 2003 ) and proliferation ( Faris et al, 2019 ; Faris et al, 2022 ), migration ( Fiorio Pla et al, 2012 ; Zuccolo et al, 2018b ), differentiation ( Maione et al, 2022 ), contraction ( Bers, 2008 ; Landstrom et al, 2017 ), metabolism ( Patella et al, 2015 ), angiogenesis ( Bernardini et al, 2019 ; Moccia et al, 2019b ; Scarpellino et al, 2020 ), vasculogenesis ( Moccia et al, 2012 ; Moccia et al, 2013 ; Zuccolo et al, 2018a ), and, more recently, neurovascular coupling ( Negri et al, 2021c ; Soda et al, 2023 ). The multifaceted nature of intracellular Ca 2+ signalling can be further appreciated by recalling that, depending on the Ca 2+ source and on the Ca 2+ -dependent target, an increase in [Ca 2+ ] i may induce opposing cellular responses, e.g., proliferation ( Faris et al, 2022 ) and apoptosis ( Astesana et al, 2021 ; Faris et al, 2023 ), vascular smooth muscle cell contraction ( Knot and Nelson, 1998 ) and relaxation ( Nelson et al, 1995 ), neuronal depolarization ( Menigoz et al, 2016 ) and hyperpolarization ( Tiwari et al, 2018 ), long-term potentiation ( Ezra-Nevo et al, 2018 ; Soda et al, 2019 ; Locatelli et al, 2021 ) and long-term depression ( Hirano, 2013 ).…”
Section: Introductionmentioning
confidence: 99%